RELIGIOUS MEANING IN SOCIAL PRACTICES: A STUDY OF MUSLIMS TOLERANT ATTITUDES IN SOUTH SULAWESI - Idris, Djamaluddin M.; Zubair, Muhammad Kamal (Indonesian Journal of Islamic Literature and Muslim Society, 2019)
This study aims to find out the patterns of tolerance of the Muslim community towards other religious communities in South Sulawesi. It also examines opportunities to overcome the barriers to building understanding among religious communities. This study employs a normative theological approach, sociology of religion, and phenomenology as well. This study reveals that the attitude of Muslim society toward other religious communities in South Sulawesi is based on several factors: [a] social integration through economic factors; [b] social integration through a diversity of cultural factors; and [c] social integration through political factors. The tolerant and harmony life among Muslim and non-Muslim communities is reflected in their social interaction due to economic interests and religious beliefs. The implication of this study is to develop social interaction among religious communities based on human and spiritual values